Internet‐based communication platform for residential DR programmes. Issue 2 (1st March 2017) - Kuzlu, Murat; Rahman, Md Moshiur; Pipattanasomporn, Manisa; Rahman, Saifur
Abstract : The objective of this study is to present the architecture and laboratory experimentation of an Internet‐based communication platform to enable residential demand response (DR) programmes that do not rely on the advanced metering infrastructure (smart meters). Technologies and software that serve as the building blocks for the proposed platform, together with the messaging architecture based on the open automated DR protocol, are discussed. Security features necessary to secure DR implementation for a residential sector are also presented. The proposed platform has been implemented in a laboratory environment to showcase how the overall system can function. The proposed Internet‐based communication platform is expected to quickly and reliably enable a large number of households to participate in DR programmes without smart meter deployment, while ensuring customer data privacy and comfort.